FEMALE BREAST MYOFIBROBLASTOMA: CASE REPORT - Delgado, Claudia Teresinha Moraes Pinheiro (Mastology, 2018)
The myofibroblastoma of the breast is rare, being even less frequent in women. It is a benign mesenchymal tumor of uncertain etiology. The present study reports the case of a 47-year-old patient with a palpable nodule on the right breast, non-painful, having appeared approximately one year before, and with slow growth, located in an inferolateral quadrant. The biopsy pathology product describes a firm, yellowish white tissue that microscopically exhibited fusocellular proliferation without atypia, including small ductal structures with epithelial hyperplasia, suggesting immunohistochemistry which revealed expression of desmin and smooth muscle actin. Based on the morphological and anatomopathological picture, the diagnosis of breast myofibroblastoma was confirmed. Sectorectomy surgery was performed as treatment